Pengaruh Proporsi Tepung Terigu Dan Tepung Ubi Jalar Ungu (Ipomoea Batatas Var Ayamurasaki) Terhadap Kadar Protein, Volume, Pengembangan Dan Mutu Organoleptik Roti Manis - Norhasanah Norhasanah; Hj. Ermina Syainah; Rifna Muzdaliafah; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2016)
Sweet bread is a food which is made from fermented wheat flour mixture and baked. Purple sweet potato has not been widely used as flour added to the sweet bread with a protein content of 2.62%, which can be recommended for the PMT-Recovery on nutritional problems KEP. The more purple sweet potato flour is added to the mixture the wheat flour less , this means that less gluten with an important role in the development volume and organoleptic sweetbreads. This study aims to analyze the influence of the proportion of wheat flour and purple sweet potato flour on the protein content, the volume and the development of organoleptic sweet bread. This study was an experimental study with RAL and three times the replication report (100%: 0%, 97.5%, 2.5%, 95%, 5%, 92.5: 7.5%, 90%: 10%). This study was conducted on 25 qualified speakers somehow STIKES Husada Borneo Banjarbaru. Receiving data for data analysis of protein levels using ANOVA, and to test the organoleptic quality (color, aroma, texture and taste) use traditional Friedman data analysis. The results showed that the average value of the highest protein content of the test on P0 (3.24%) and the lowest in the P4 (2.92%), the average value of the test volume higher P0 (35.58) and the lowest in P4 (25.42%) and the maximum development at P0 (36.5%) and the lowest in Q4 (24.7%) significantly influenced the sweet bread product as p <α = 0.05. Sweetbreads organoleptic quality tests that include the color with the highest average in P3 (3.28%) and the lowest in the P4 (2.92%), flavor with the highest average value P0 (3.24% ) and the lowest on P4 (2.76%), the texture with the highest average value to P0 (3.4%) and the lowest in the P4 (2.44%), taste with the smallest average high in P3 (3.32%) and lowest in the P4 (3.04%). Poses the most preferred by the speakers is P3 proportion of flour and flour purple sweet potato that is 92.5%: 7.5%.